Post partum depression: is it associated to gender based violence? - Escobar, Juan (2009)
Introduction: Post partum depression and gender based violence are very common disorders in women; the importance of early diagnosis and prompt treatment is to avoid future consequences in women, newborns and the family. Objectives: To determine the association between post partum depression and gender based violence. Design: Exploratory cross-sectional. Place: Hospital Nacional Docente Madre Niño San Bartolome, Lima, Peru. Participants: Post partum women. Interventions: We applied a sociodemographic data and delivery card, the Edinburgh scale, revised inventory predictors of post partum depression and an instrument for detection of gender based violence to 100 women 1 to 12 months post partum. Data analysis was conducted using odds ratio tests, Chi-square and Fisher exact test. Main outcome measures: Association between post partum depression and gender based violence. Results: The rate of post partum depression was 17% with statistical difference between the cases of post partum depression and self-esteem, depression before pregnancy, anxiety during pregnancy, marital satisfaction and stressful events during pregnancy. Moreover, 51% of women were victims of gender based violence, mainly psychological and the husband being the principal aggressor. The cases of gender based violence and post partum depression were found significantly different (p=0,001). Also, statistical differences were found between depression post partum y gender based violence during pregnancy, OR 5,5 (CI: <5,5; 16,7>). Conclusions: There is increased risk of depression post partum in women victims of violence.